8 - The Journey of Wamba dia Wamba and the Struggles for Emancipatory Politics in Africa - Campbell, Horace G. (Africa Development, 2020)
This tribute centralises Ernest Wamba dia Wamba’s commitment to committed scholarship, including his contributions to the challenges faced in the quest for popular democracy in Africa, in the emancipatory project. Tracing his journey from the village community with the remnants of the palaver and mbongi through the Dar es Salaam School, this homage highlights his contribution to the understanding of African philosophy. His immersion in the experiences of the Sovereign National Conference and his foray into the multi-sided struggles for a new mode of politics distinguished Wamba from intellectuals who pontificated about the struggles against militarism from the safety of seminar rooms. This celebration of his life echoes his call for the importance of re-dynamising African cultures in the process of restoring the humanity of Africans.